Electrodeposition immobilized molybdenum disulfide quantum dots and their electrochemiluminescence application in the detection of melamine residues in milk powder. Issue 19 (26th April 2021) - Ye, Yousheng; Li, Shasha; Ping, An; Wan, Xinjun; Li, Jianguo
Abstract : In this paper, one-step hydrothermal and electrodeposition methods were used to prepare a MoS2 quantum dot (QD) solid-phase electrochemiluminescent (ECL) electrode for the detection of melamine residues in milk powder. Abstract : In this paper, one-step hydrothermal and electrodeposition methods were used to prepare a MoS2 quantum dot (QD) solid-phase electrochemiluminescent (ECL) electrode for the detection of melamine residues in milk powder. With the assistance of chitosan, MoS2 QDs fixed by the one-step electrodeposition method show better ECL performance than those by traditional deposition methods due to better dispersibility and stability. Based on the quenching of the MoS2 QDs ECL signal by melamine, quantitative detection of melamine in the sample was performed. The structure and morphology of a MoS2 -CHIT/indium tin oxide (ITO) solid-phase ECL electrode were characterized by TEM and XPS, and melamine was detected by the ECL method using a three-electrode system. The proposed sensor exhibited good linearity in the range of 1.00 × 10 −11 to 1.00 × 10 −7 mol L −1 (Δ I = 12 100.62 + 1009.93 lg c (mol L −1 ), R 2 = 0.997), and the method shows the advantages of simplicity and sensitivity compared to traditional detection methods. The interference of common ions in milk powder on the modified electrode was within 5%, and the recovery rate of real sample detection was within 97–98%. As a result, the proposed method is suitable for detecting melamine residues in milk powder.